2010
DOI: 10.1007/s10532-010-9370-z
|View full text |Cite
|
Sign up to set email alerts
|

Multisubstrate kinetics of PAH mixture biodegradation: analysis in the double-logarithmic plot

Abstract: The proposed method of kinetic analysis of aqueous-phase biodegradation of polycyclic aromatic hydrocarbons (PAH) mixture presupposes representation of kinetic curves for each pair of mixture components, S(x) and S(y), in double-logarithmic coordinates (ln S(x); ln S(y)). If PAH mixture conversion corresponds to the multisubstrate model with a common active site, then the graphs in double-logarithmic coordinates are straight lines with the angular coefficients equal to the ratio of respective first-order rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 22 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Investigations conducted with enrichment consortia or individual microbial strains have shown that if a common enzymatic pathway for degradation exists, mixture effects can be positive (mixture enhances degradation of individual chemicals), because of stimulation of biomass growth and co-metabolism, or negative (mixture reduces degradation of individual chemicals), because of competitive inhibition leading to preferential degradation (Stringfellow and Aitken 1995;Guha et al 1999;Knightes and Peters 2006;Desai et al 2008;Baboshin and Golovleva 2011). Stimulation of biomass growth and competitive inhibition have been described by multisubstrate models (Guha et al 1999;Knightes and Peters 2006;Desai et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations conducted with enrichment consortia or individual microbial strains have shown that if a common enzymatic pathway for degradation exists, mixture effects can be positive (mixture enhances degradation of individual chemicals), because of stimulation of biomass growth and co-metabolism, or negative (mixture reduces degradation of individual chemicals), because of competitive inhibition leading to preferential degradation (Stringfellow and Aitken 1995;Guha et al 1999;Knightes and Peters 2006;Desai et al 2008;Baboshin and Golovleva 2011). Stimulation of biomass growth and competitive inhibition have been described by multisubstrate models (Guha et al 1999;Knightes and Peters 2006;Desai et al 2008).…”
Section: Introductionmentioning
confidence: 99%